Open‐label pilot study of lisdexamfetamine for cocaine use disorder. (4th May 2021) - Mariani, John J.; Choi, C. Jean; Pavlicova, Martina; Mahony, Amy L.; Brooks, Daniel J.; Grabowski, John; Levin, Frances R.
ABSTRACT: Background : Cocaine use disorder (CUD) is a substantial public health problem with no FDA-approved medication treatments. Psychostimulants have shown promise as pharmacotherapy for CUD. Lisdexamfetamine, a novel prodrug psychostimulant, is roughly 40–50% as potent as dextroamphetamine. Objectives : To evaluate the safety, tolerability, and optimal dosing of lisdexamfetamine for treating CUD. Methods : Open-label, 8-week trial of 17 CUD adults. Participants were titrated to the maximum tolerated dose of 140 mg over 2-week period and maintained for 4 weeks, followed by a two-week taper period. The primary outcome measures were the maximum daily dose achieved during the study period and tolerability as measured by medication-related study drop-out. Results : Among the 16 participants with post-enrollment data, the mean dose of lisdexamfetamine achieved was 118.1 mg (standard deviation (SD) = 40.4), mean retention was 6.5 weeks (SD = 2.0), and no participants discontinued study medication due to adverse effects. Four participants had dose reductions due to adverse effects and continued in the trial. Six participants (37.5%) were abstinent for the last 3 weeks of their study participation. Mean dollars of cocaine spent per day significantly decreased from $19.72 at baseline to $7.57 during the last 3 weeks of study participation ( t15  = 3.60, p = .003). The mean percent of using days significantly decreased from 25% at baseline to 12% during the last 3 weeks of study participation ( t15  = 3.33, p = .005). Conclusion : The use of lisdexamfetamine for CUD in doses ranging to 140 mg daily was safe and generally well tolerated.